Steady state kinetic studies of initiation of RNA synthesis on T7 DNA in the presence of rifampicin. - Smagowicz, J W (1977)
The steady state kinetics of initiation of T7 DNA transcription by RNA polymerase holo enzyme from E. coli in the presence of rifampicin and the two substrates ATP and UTP were studied. Under these conditions, the enzyme catalyzes exclusively the promotor specific synthesis of pppApU. The kinetic data are in agreement with the mechanism of a truly ordered reaction. Binding of the initiating nucleotide ATP to the transcriptional complex occurs prior to the binding of the substrate UTP. Release of pppApU is most probably the rate limitinig step. Km constants were found to be 0.6 mM for ATP and 0.31 mM for UTP, respectively. The substrate inhibition pattern indicated that the substrate site exhibits a finite affinity for incorrect nucleoside triphosphate (Ki = 2.3 mM). A similar non specific binding to the 3-OH site could not be demonstrated.